Evaluation and attribution of historical surface air temperature changes over China simulated by coupled and uncoupled models - Zuo, Ling; Li, Lijuan; Wang, Bin; Feng, Tao; Chang, Youli (Frontiers in Earth Science, 2023)
The increase in the average surface air temperature anomaly (SATA) over China is stronger than the global average. However, the accurate simulation and attribution of regional SATA evolution remain challenging for current global climate models. This study simulates historical SATA variations over China using the coupled (FGOALS-g3) and uncoupled (atmospheric component, GAMIL3) models and examines their possible causes. Results show that both models reproduce the historical SATA variation with a higher correlation coefficient than many global climate models, although they somewhat over- or underestimate changes in different periods. In particular, the cooling trend during 1941–1970 is well simulated by the coupled model but scarcely present in the uncoupled model. In addition, the coupled simulations produce stronger trends (closer to the reanalysis dataset) and interannual variations by allowing full interaction between the atmosphere, ocean, and sea ice. In contrast, the uncoupled simulations reproduce better decadal and multi-decadal variations, e.g., Atlantic Multidecadal Oscillation, owing to the constraints of the observed sea surface temperature (SST) and sea ice cover. Using Detection and Attribution Model Intercomparison Project (DAMIP) experiments, we find that the warming in the early 20th century and the recent 50 years is mainly driven by natural forcings and greenhouse gases (GHGs), whereas the cooling during 1941–1970 is caused by natural factors and anthropogenic aerosols. The cooling effects of anthropogenic aerosols are mainly from the indirect SST-mediated responses through the atmosphere-ocean interactions in the coupled models